Low Oct4 expression in mesenchymal stem cells contributes to the development of the bone marrow pre-metastatic niche in advanced breast cancer patients - Sanmartin, Cecilia (2021)
The imbalance between osteogenesis and osteoclastogenesis in the bone marrow (BM) microenvironment seems to play an essential role in the establishment of bone metastasis in untreated advanced breast cancer patients (BCP). We have previously found that this lack of balance is produced, among other factors, by a lower self-renewal, proliferation, and osteogenic differentiation capacity of BM-mesenchymal stem cells (MSCs). Mechanisms mediating these characteristic changes remain elusive. Here, we evaluated the expression of the osteoprogenitor marker CD146 (Flow cytometry), telomerase activity (qPCR), telomere length (qPCR), as well as the expression of the pluripotency factors Oct4 and Sox2 (qPCR) in BM-MSCs from clinical stage IIIb BCP (n=8) vs. healthy volunteers (HV; n=8). We found that MSCs from BCP had lower percentage of CD146+ cells (p=0.04), decreased CD146 relative fluorescence index (p=0.002), lower telomerase activity (p=0.04), and shortened telomere length (p=0.002) compared with HV. Moreover, Oct4 and Sox2 expression decreased by 54% (p=0.03) and 72% (p=0.009) in BCP-MSCs, respectively. Interestingly, Oct4 silencing impaired the ability of BM-MSCs to differentiate into osteoblasts (p<0.0001). In conclusion, we found that a low Oct4 expression characterizes the altered BM-MSC phenotype in BCP. This change may explain the loss of osteoprogenitors and the impairment of MSC osteogenic processes, which create an ideal environment for BM metastatic development.